2020
DOI: 10.1007/s00520-020-05337-9
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-related fatigue and its determinants in a cohort of women with breast cancer: the DAMA Cohort

Abstract: Cancer-related fatigue (CRF) is one of the most prolonged discomforts suffered by people who have had cancer. Seventy-eight to ninety-six percent of cancer patients experience fatigue, especially while undergoing treatment. CRF is related to insomnia, anxiety, depression, and also varies depending on age. However, little is known about the factors contributing to CRF and better understanding of determinants of CRF makes it easier to identify early patients at risk and in designing intervention planning. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…Less is known about the relationship between anxiety and fatigue severity. Our findings are consistent with previous reports that found that higher rates of trait anxiety were associated with higher levels of fatigue in patients with breast cancer undergoing chemotherapy [68] and in cancer survivors [32,52,65]. One explanation for this association is that higher levels of anxiety cause dysregulation of the hypothalamic-pituitary-adrenal axis, which may increase cytokine production and associated increases in both cognitive and physical fatigue [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Less is known about the relationship between anxiety and fatigue severity. Our findings are consistent with previous reports that found that higher rates of trait anxiety were associated with higher levels of fatigue in patients with breast cancer undergoing chemotherapy [68] and in cancer survivors [32,52,65]. One explanation for this association is that higher levels of anxiety cause dysregulation of the hypothalamic-pituitary-adrenal axis, which may increase cytokine production and associated increases in both cognitive and physical fatigue [8].…”
Section: Discussionsupporting
confidence: 92%
“…Within the context of undergoing chemotherapy, it is readily apparent why patients with the additional burden of child care would be classified in the High class. A plausible explanation for the associations between the other two characteristics and membership in the High class is the recent findings that perceptions of lack of social support and loneliness are associated with higher levels of cancer-related fatigue [52,59]. While it is difficult to disentangle the causal relationships between lack of social support and cancer-related fatigue, future studies should incorporate measures of loneliness, social isolation, and social support to evaluate these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, numerous studies have been conducted aiming to explore this association, and different hypotheses have been formulated. 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 According to Reuter and Härter, 46 CRF could be interpreted as part of a depressive disorder where somatic symptoms play a central role. Conversely, Jacobsen et al.…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 , 33 Previous studies documented that CRF and depression could coexist in cancer patients, however their possible association and interconnection remain not well established. 15 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 Results of these studies have, in fact, demonstrated that when CRF was considered as a one-dimensional construct, it could be a simple symptom of depression; on the contrary, considering CRF in a multidimensional way, it resulted in a syndrome with complex relationships with depressive disorders. In particular, emotional aspects and the inner tension of patients with fatigue present similarities with anhedonia and psychomotor agitation, typical of depressive syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Last, the conditional parallel-process LGM with baseline PTSS (i.e., avoidance, intrusion, and hyperarousal) as predictors was examined. Anxiety, depressive symptoms, and chronotype were entered as covariates in the research model given the association of anxiety with sleep 23 and fatigue 24 and that of depression 23 with SD and fatigue 1 and that of chronotype with sleep 25 and fatigue. 26 To examine the statistical significance of indirect effects in the conditional parallel-process LGM, bias-corrected 95% confidence intervals (CIs) were estimated using 5000 bootstrapping.…”
Section: Second Twomentioning
confidence: 99%